การประยุกต์ใช้หลักอริยสัจ ๔ ในการแก้ไขปัญหาชีวิต - สารกิจประยุต พระครู (Dhammathas Academic Journal, 2017)
บทคัดย่อ บทความวิชาการเรื่องนี้ มีวัตถุประสงค์เพื่อศึกษาการประยุกต์ใช้หลักอริยสัจ ๔ ในการแก้ไขปัญหาชีวิต พบว่า หลักอริยสัจ ๔ เป็นธรรมเครื่องดับทุกข์เป็นไปในลักษณะของการวิเคราะห์ของการแก้ไขปัญหาให้ถูกต้องด้วยวิธีการและถูกจุด คือ การรู้เท่าทันปัญหามี ๔ ด้าน ได้แก่ ๑) ทุกข์ ๒) สมุทัย ๓) มรรค และ ๔ นิโรธ ทุกข์ คือ ความไม่สบายกาย ไม่สบายใจมีลักษณะบีบคั้น ทนได้ยาก สมุทัย เหตุให้เกิดทุกข์ ได้แก่ ตัณหา ๓ มรรค เป็นข้อปฏิบัติให้ถึงความดับทุกข์ความดับทุกข์ ได้แก่ มรรค ๘ ประการ เป็นหนทางการดับทุกข์ และ นิโรธ คือการดับทุกข์ ได้แก่ การดับทุกข์หรือกิเลสตัณหาให้สิ้นไป การประยุกต์ใช้หลักอริยสัจ ๔ ในการแก้ไขปัญหาชีวิต คือการวิเคราะห์ปัญหา และแก้ไขปัญหาให้ถูกจุด โดยวิธีการที่ถูกต้องนั่นเอง เช่น เมื่อเราปวดท้อง เป็นทุกข์ จากนั้นให้วิเคราะห์หาสาเหตุของการปวดท้อง และไม่กลับไปทำซ้ำอีก (สมุทัย) ปวดท้องเพราะรับประทานผักดอง และจะไม่กลับไปรับประทานอีก จากนั้นหาหนทางรักษาอย่างถูกวิธีนั่นก็คือการไปพบแพทย์ (มรรค) จากนั้นแพทย์ก็จะทำการรักษา เราก็จะหายจากอาหารปวดท้อง (นิโรธ) ถึงการดับทุกข์โดยสิ้นเชิง Abstract The academic article was purposed to study the application of the Four Noble Truths for life problem solving. The found that the Four Noble Truths were the cessation of suffering, which was characterized by analysis of problem solution that was right and direct to the principle. That was, acknowledgement of the problem was comprised of 4 aspects: 1) suffering (Dukkha), 2), the cause of suffering (Samudaya), 3) the path (Magga), and 4) the cessation of suffering (Nirodha). Suffering (Dukkha) was the physical painand the mental displeasure with oppress and impatience in nature, the cause of suffering (Samudaya) was referred to three kinds of craving (Tanha), the path leading to the cessation of suffering (Magga) was called the Noble Eightfold Path, and the cessation of suffering (Nirodha) was the extinction of defilements and cravings. The application of the Four Noble Truths for life problem solution was the problem analysis and direct problem solving through right solutions. For example, when a person got a stomachache, he felt severely painful (Dukkha). After that, he analyzed and found the cause of a stomachache and he decided not to repeat that again (Samudaya). In case he knew he got a stomachache because of pickled vegetable and he decided not to have it again. Then, he found the right way to heal his pain by going to see the doctor (Magga). After the doctor healed him, he recovered from illness (Nirodha) and the pain from a stomachache absolutely disappeared.